The metaverse in nuclear medicine: transformative applications, challenges, and future directions - Tang, Yufu; Liang, Hongying; Yang, Xin; Xue, Xiangming; Zhan, Jingming (Frontiers in Medicine, 2024)
The metaverse, a rapidly evolving virtual reality space, holds immense potential to revolutionize nuclear medicine by enhancing education, training, diagnostics, and therapeutics. This review explores the transformative applications of the metaverse in nuclear medicine, where immersive virtual learning environments, simulation-based training, artificial intelligence (AI)-powered decision support systems integrated into interactive Three-Dimensional(3D) visualizations, and personalized dosimetry using realistic patient-specific virtual models are seamlessly incorporated into the metaverse ecosystem, creating a synergistic platform for healthcare professionals and patients alike. However, the responsible and sustainable adoption of the metaverse in nuclear medicine requires a multidisciplinary approach to address challenges related to standardization, accessibility, data security, and ethical concerns. The formation of cross-disciplinary consortia, increased research and development (R&D) investment, and the strengthening of data governance and cybersecurity measures are crucial steps in ensuring the safe and effective integration of the metaverse in healthcare. As the metaverse continues to evolve, researchers, practitioners, and policymakers must collaborate and explore its potential, navigate the challenges, and shape a future where technology and medicine seamlessly integrate to enhance patient care and outcomes in nuclear medicine. Further research is needed to fully understand the implications of the metaverse in clinical practice, education, and research, as well as to develop evidence-based guidelines for its responsible implementation. By embracing responsible innovation and collaboration, the nuclear medicine community can harness the power of the metaverse to transform and improve patient care.